Evaluation of a carers' information programme culturally adapted for South Asian families. (2nd August 2017) - Parveen, Sahdia; Blakey, Heather; Oyebode, Jan R.
Abstract : Objectives: The Alzheimer's Society has culturally adapted an Information Programme for South Asian families (IPSAF) who support an individual living with dementia. The objectives of this evaluation were to establish whether IPSAF had an immediate and medium‐term impact on those who attended and how it impacted on the wider family and the person with dementia. Methods: An inclusive, pluralistic approach was adopted. Seven focus groups were conducted with 42 participants, and 37 participated in a pre‐post knowledge quiz. Seven family interviews were conducted with 17 participants, and 3 families were followed up after 6 months. Thematic analysis was conducted on the data. Findings: The IPSAF was found to improve participants' knowledge of dementia leading to increased understanding of the person with dementia. Participants became more aware of available services and accessed services to make use of practical support. IPSAF was reported to have an impact for people living with dementia, with carers' newfound understanding resulting in some changes in care practice that promoted empowerment and independence for people living with dementia. There was also some evidence to suggest that IPSAF had an impact on the wider family, with participants sharing information about dementia with family members who had not attended the programme. Families were continuing to make changes to improve the lives of people living with dementia 6 months later, suggesting IPSAF had a sustained impact. Conclusion: This culturally adapted programme was found to have a significant impact on carers, the person with dementia, and the wider family.